2018
DOI: 10.1155/2018/3932643
|View full text |Cite
|
Sign up to set email alerts
|

Use of Telemedicine in Addiction Treatment: Current Practices and Organizational Implementation Characteristics

Abstract: Telemedicine applications offer innovative approaches for treating and reducing the effects of substance use disorders (SUDs). This analysis assessed the interest in and use of 11 telemedicine applications in a sample of 363 SUD organizations in the United States of America. Fifty percent of the organizations expressed high rates of interest in seven of the telemedicine applications, demonstrating the appeal of telemedicine within this field. The top three self-reported telemedicine applications being used wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…These services can be used to provide capabilities for alcohol counseling and addiction treatment and give patients 24/7 access to care, and they allow for closer surveillance of patients at risk for decompensation and relapse. (41)(42)(43) A recent pilot study has shown that specialized hepatology care can be effectively delivered through telehealth to distant communities not originally serviced by transplant and hepatology centers. (44) Providers should schedule more frequent telehealth visits for high-risk patients to mitigate the effects of social isolation and AUD treatment disruption.…”
Section: What Can Be Done Now?mentioning
confidence: 99%
“…These services can be used to provide capabilities for alcohol counseling and addiction treatment and give patients 24/7 access to care, and they allow for closer surveillance of patients at risk for decompensation and relapse. (41)(42)(43) A recent pilot study has shown that specialized hepatology care can be effectively delivered through telehealth to distant communities not originally serviced by transplant and hepatology centers. (44) Providers should schedule more frequent telehealth visits for high-risk patients to mitigate the effects of social isolation and AUD treatment disruption.…”
Section: What Can Be Done Now?mentioning
confidence: 99%
“…The APA telepsychiatry toolkit observes that certain patient groups (e.g., children and adolescents in the autism spectrum, patients with disabling anxiety) can show greater acceptance for telepsychiatry services. 28 , 29 Although telemedicine applications have been used for computer-based screening assessments, telephone-based recovery supports, and telephone-based therapy for addictive disorders, 30 its use is limited otherwise. Hence, app-based interventions for a variety of interventions from craving management to supervised medications require further consideration.…”
Section: Evidence For Telemental Health Servicesmentioning
confidence: 99%
“…Despite these emerging trends, the actual adoption of telephonic and video SUD services has been slow [ 7 , 13 ]. Emerging data suggest that organization type (eg, health system, specialty treatment clinics, etc) [ 19 ] and location (eg, suburban, rural, urban, etc) [ 20 ] can potentially influence the readiness to use these technologies.…”
Section: Introductionmentioning
confidence: 99%